Robot Facial Expression Framework for Enhancing Empathy in Human-Robot Interaction - PARK UNG; MINSOO KIM; Youngeun Jang; GiJae Lee; KangGeon Kim; KIM, IG JAE; JongSuk Choi (2021 30TH IEEE INTERNATIONAL CONFERENCE ON ROBOT AND HUMAN INTERACTIVE COMMUNICATION (RO-MAN), 2021)
A social robot interacts with humans based on social intelligence, for which related applications are being developed across diverse fields to be increasingly integrated in modern society. In this regard, social intelligence and interaction are the keywords of a social robot. Social intelligence refers to the ability to control interactions or thoughts and feelings of relationships with other people; primal empathy, which is the ability to empathize by perceiving emotional signals, among the components of social intelligence was applied to the robot in this study. We proposed that the empathic ability of a social robot can be improved if the social robot can create facial expressions based on the emotional state of a user. Moreover, we suggested a framework of facial expressions for robots. These facial expressions can be repeatedly used in various social robot platforms to achieve such a strategy.